1977
DOI: 10.1111/j.1399-6576.1977.tb01219.x
|View full text |Cite
|
Sign up to set email alerts
|

Halothane Anaesthesia and Suxamethonium II The Significance of Preoperative Gallamine Administration

Abstract: Preoperative administration of gallamine was evaluated during inhalation anaesthesia with nitrous-oxide and halothane with two administrations of suxamethonium 1 mg/kg body weight, 5 min apart. Sixty healthy patients were randomly divided into three groups and preanaesthetic gallamine, 0.3, 0.4 or 0.5 mg/kg body weight, respectively was administered intravenously 3 min before induction, according to the allocation. Just before induction of anaesthesia the patients were examined for signs and symptoms of partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
2

Year Published

1978
1978
1982
1982

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(9 reference statements)
0
2
2
Order By: Relevance
“…The arrhythmias were more frequent in the higher atropine dosage groups, and in some of the patients they were serious (Fig, 4). These results contrast sharply with our previous findings that no ventricular arrhythmias occurred following a second dose of suxamethonium in 120 patients given either atropine or gallamine 5 rnin before induction (VIBY-MOGENSEN et al 1976, WISBORG et al 1977.…”
Section: Cardiac Rhythmcontrasting
confidence: 99%
See 1 more Smart Citation
“…The arrhythmias were more frequent in the higher atropine dosage groups, and in some of the patients they were serious (Fig, 4). These results contrast sharply with our previous findings that no ventricular arrhythmias occurred following a second dose of suxamethonium in 120 patients given either atropine or gallamine 5 rnin before induction (VIBY-MOGENSEN et al 1976, WISBORG et al 1977.…”
Section: Cardiac Rhythmcontrasting
confidence: 99%
“…We have shown previously, however, that preanaesthetic intravenous injection of atropine before halothane inhalation anaesthesia does not protect against severe bradycardia following the second dose of suxamethonium, unless doses of atropine are used which cause potentially dangerous tachycardia (VIBY-MOGENSEN et al 1976). In another study we found that precurarization with gallamine does not give any reliable protectionnot even in doses causing marked tachycardia and an otherwise unacceptable incidence of side effects (WISBORG et al 1977).…”
mentioning
confidence: 91%
“…Thus 12 (15%) out of 80 patients given atropine 0.01 mg/kg or more (95% confidence limits: 8.00-24.78%) developed ventricular arrhythmias occurring after the second injection of suxamethonium. These results contrast sharply with our previous findings that no ventricular arrhythmias occurred following a second dose of suxamethonium in 120 patients given either atropine or gallamine 5 rnin before induction (VIBY-MOGENSEN et al 1976, WISBORG et al 1977. 4).…”
Section: Gardiac Rhythmcontrasting
confidence: 99%
“…Several methods have been proposed to prevent this bradycardia : for example, the preanaesthetic administration of atropine or a small dose of a nondepolarizing muscle-relaxant (LEIGH et al 1957, LUPPRIAN & CHURCHILL-DAVIDSON 1960, KARHUNEN et al 1972. In another study we found that precurarization with gallamine does not give any reliable protectionnot even in doses causing marked tachycardia and an otherwise unacceptable incidence ofside effects (WISBORG et al 1977). In another study we found that precurarization with gallamine does not give any reliable protectionnot even in doses causing marked tachycardia and an otherwise unacceptable incidence ofside effects (WISBORG et al 1977).…”
mentioning
confidence: 86%